Bone cement implantation syndrome: A dreaded complication during arthroplasty - Jaspreet Kaur Nagpal; Pramod Madhav Velankar; Sandeep Choudhary; Venkatesh Nutangi (Medical Journal of Dr. D.Y. Patil University, 2015)
Bone cement implantation syndrome is a known cause of intraoperative morbidity and mortality in patients undergoing cemented arthroplasty. It is a rare but potentially fatal complication. A case of elderly female patient is reported who developed this complication during hemi arthroplasty of right hip. Within a few minutes of cementation, she developed severe hemodynamic derangement and shock with hypoxemia. Aggressive and early resuscitative measures led to a favorable outcome. Risk factors, etiopathogenesis and management of this condition are discussed in brief.